3d–4f Heterometallic cluster incorporated polyoxoniobates with magnetic properties. Issue 69 (9th August 2021) - Lin, Yu-Diao; Ge, Rui; Tian, Chong-Bin; Sun, Cai; Sun, Yan-Qiong; Zeng, Qing-Xin; Li, Xin-Xiong; Zheng, Shou-Tian
Abstract : A series of 3d–4f heterometallic cluster incorporated polyoxoniobates (PONbs) were first made and characterized, demonstrating an ideal model to probe how transition-metal ions influence the magnetic properties of PONbs. Abstract : A series of 3d–4f heterometallic cluster incorporated polyoxoniobates (PONbs) with different magnetic properties were first made and characterized. This work not only provides a promising strategy to make new heterometallic cluster incorporated PONbs but also demonstrates an ideal model to probe how transition-metal ions influence the magnetic property of PONbs.